Μετάφραση και Σχολιασμός Αποσπάσματος του "Women in Classical Islamic Law: A Survey of the Sources", της Susan A. Spectorsky - (:unkn) unknown (My University, 2020)
Η παρούσα πτυχιακή εργασία αποτελεί ένα δείγμα μετάφρασης πρωτότυπου περιεχομένου και εκτενούς σχολιασμού της μεταφραστικής διαδικασίας και των αναδυόμενων μεταφραστικών προβλημάτων. Η θεματική του κειμένου εστιάζει στη θέση των γυναικών ως προς τον γάμο και τον άνδρα, όπως αυτή ορίζεται από το ιερό βιβλίο των μουσουλμάνων, το Κοράνι. Δεν αποτελεί ένα αμιγώς θρησκευτικό κείμενο, αλλά ένα κράμα κοινωνικής και επιστημονικής έρευνας βασισμένη σε αληθινά τεκμήρια.

This dissertation is a translation of original content and an extensive commentary on the translation process and on the emerging translative problems. The theme of the text focuses on the role of women in marriage and towards to their husbands, as defined by the central religious text of Muslims, Qur'an. It is not a purely religious text, but a mixture of social and scientific research based on real facts.
Translation and Comments on "Women in Classical Islamic Law: A Survey of the Sources" by Susan A. Spectorsky
Keywords: μετάφραση, σχολιασμός, μεταφραστική διαδικασία, γυναίκες, Ισλαμικός νόμος, Ισλάμ, Κοράνι, εδάφιο; translation, comments, translation process, women, islamic law, Islam, Quran, verses